Investigation of SEN virus prevalence in hemophilia patients - Davod Javanmard; Motahareh Mahi-Birjand; Effat Alemzadeh; Mahdie Mohammadi; Masood Ziaee (New Microbes and New Infections)
Background: Hemophilia and transfusion-dependent patients are at high risk of a wide range of blood-borne agents. Among these, SEN virus (SENV) stands out as a significant concern due to its association with transfusion-induced non-A to non-E hepatitis. This study, therefore, aimed to investigate the prevalence of this virus in hemophilia patients, focusing on potential complications and risk factors. Method: This was a cross-sectional study conducted in a hemophilia center in the east of Iran. Blood samples were taken from patients and healthy people, and demographic and clinical information was collected. The sera samples were then subjected to DNA extraction. PCR-based methods detected SENV and its genotype, and then phylogenetic analysis was performed. The collected data were analyzed and interpreted by SPSS22 software. Results: The mean age of patients and the healthy group was 26.18 ± 14.97 and 41.69 ± 14.05, respectively. Among the patient and healthy groups, 94.5 % and 36.4 % were male, and the rest were female, respectively. Most of the participants in the patient group had hemophilia type A (85.5 %), then type B (7.3 %), VWD type (3.6 %), and F and plt type (1.8 %) were in the next categories. SENV-DNA was detected in 58.2 % of patients and 20 % of healthy groups (P-value: 0.00). Among these, H and D genotypes were found in 35 % and 23.7 % of patients and 12.7 % and 7.3 % of healthy groups, respectively. The prevalence of the virus was significantly related to minor elevation of AST and was higher in hemophilia type A (63.8 %) and severe type of disease (63.2 %). Conclusion: This study underscore the significant prevalence of the SENV virus in hemophilia patients, a particularly noteworthy finding compared to the healthy population. With the limited information available about this virus, our findings highlight the importance of continuous monitoring and follow-up of high-risk groups in relation to blood-borne pathogens, providing reassurance about the ongoing efforts in the field.